2019
DOI: 10.1007/978-3-030-15096-9_18
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of the N-BBM Process

Abstract: The Branching Brownian Motions (BBM) are particles performing independent Brownian motions in R and each particle at rate 1 creates a new particle at her current position; the newborn particle increments and branchings are independent of the other particles. The N-BBM starts with N particles and at each branching time, the leftmost particle is removed so that the total number of particles is N for all times. The N-BBM was proposed by Maillard and belongs to a family of processes introduced by Brunet and Derrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…We construct the solution as the limit of a sequence (u n ) n≥1 , where each u n is the solution of a Fisher-KPP equation with same initial condition, but with a different non-linear term. Recent results of De Masi et al [5] show that this global solution can be identified with the hydrodynamic limit of the so-called N -BBM, i.e. a branching Brownian motion in which the population size is kept constant equal to N by killing the leftmost particle at each branching event.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…We construct the solution as the limit of a sequence (u n ) n≥1 , where each u n is the solution of a Fisher-KPP equation with same initial condition, but with a different non-linear term. Recent results of De Masi et al [5] show that this global solution can be identified with the hydrodynamic limit of the so-called N -BBM, i.e. a branching Brownian motion in which the population size is kept constant equal to N by killing the leftmost particle at each branching event.…”
mentioning
confidence: 89%
“…existence of a solution on a time interval [0, T ] for some T > 0), under the additional assumptions that ω is absolutely continuous with respect to Lebesgue measure with probability density φ ∈ C 2 c (R), and that there exists µ 0 ∈ R such that φ(µ 0 ) = 0, φ ′ (µ 0 ) = 1 and ∞ µ 0 φ(x) dx = 1. In [5], De Masi et al study the hydrodynamic limit of the N -BBM and its relationship with the free boundary problem (FBP ′ ). The N -BBM is a variant of branching Brownian motion in which the number of active particles is kept constant (and equal to N ) by removing the leftmost particle each time a particle branches.…”
Section: Contextmentioning
confidence: 99%
See 3 more Smart Citations